Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jcal.12616
|View full text |Cite
|
Sign up to set email alerts
|

Compensating the socioeconomic achievement gap with computer‐assisted instruction

Abstract: Background. As educational digital technologies are increasingly being used in schools, past research left unanswered the question of these technologies' impact on the socioeconomic achievement gap even when equal access is guaranteed.Objectives. The objectives of the present study are to examine whether and how the socioeconomic achievement gap can be reduced through the use of computer-assisted instruction (CAI).Methods. We addressed this issue experimentally by comparing CAI to conventional teacherled class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Others found that initially low-performing students 46 and students with lower working memory capacity 47 learned less than their more competent peers when using technology-enabled personalized learning systems. Experimentally addressing the question whether computer-assisted instruction can narrow the SES achievement gap, Chevalère et al 48 found that students from low- and high-SES backgrounds benefited equally from such instruction in comparison to conventional teacher-led instruction. Importantly, even though the SES achievement gap remained the same, low-SES students receiving computer-assisted instruction performed comparably well to high-SES students receiving conventional instruction.…”
Section: Personalized Learning: the Revival Of A Multifaceted Conceptmentioning
confidence: 99%
“…Others found that initially low-performing students 46 and students with lower working memory capacity 47 learned less than their more competent peers when using technology-enabled personalized learning systems. Experimentally addressing the question whether computer-assisted instruction can narrow the SES achievement gap, Chevalère et al 48 found that students from low- and high-SES backgrounds benefited equally from such instruction in comparison to conventional teacher-led instruction. Importantly, even though the SES achievement gap remained the same, low-SES students receiving computer-assisted instruction performed comparably well to high-SES students receiving conventional instruction.…”
Section: Personalized Learning: the Revival Of A Multifaceted Conceptmentioning
confidence: 99%